Manajemen Full Day School dalam Pembentukan Karakter Siswa di SMP Yadika Bangil Full Day School - Khoirul Anwar; Ashari Ashari (Jurnal Budi Pekerti Agama Islam, 2025)
Based on the results of the study, it can be concluded: 1) curriculum planning for the full day school program refers to the quality standards of the school's uniqueness. Schools also make learning unit programs and lesson plans (RPP) in accordance with the SKL. The school also makes a work program based on the SKL, 2) Based on the findings of the FDS system curriculum at Yadka Bangil Junior High School, it can be seen that this school seeks to liven up an Islamic atmosphere as part of learning. Student activities at this school begin at 06.45 WIB with morning activities. Duha prayer, Recitation and GLS), opening and apperception, tahfiz (memorization of the Koran) and delivery of subject matter interspersed with the term Zuhur prayer. The activity ended at 15.30 WIB with recitations (reading the Koran) and Asr prayers. The midday and Asr prayers are carried out in congregation in the mosque by teachers and students, Duha prayers are also carried out by students in turns and accompanied by teachers. The clothes of the teachers and employees are adjusted to the rules in Islam plus the rules of etiquette for communicating with the opposite sex. All of these activities are in accordance with the curriculum function created by SMP Yadika Bangil, namely the cultivation of values, mental adjustment and prevention of negative things, 3) The implementation of a full day school program in the formation of children's character can be implemented through discipline applied in habituation, example. , strengthening, and fun learning. By implementing this method, the formation of a good character for children at SMP Yadika Bangil can be achieved.